2020
DOI: 10.31774/2222-1816-2020-2-151-162
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Effect on Yield and Quality of Spring Barley in Priazov Zone in Rostov Region

Abstract: Цель: выявить влияние погодных факторов на урожайность и содержание белка в зерне ярового ячменя в условиях Приазовской зоны Ростовской области. Материалы и методы: исследования проводились в Аксайском районе Ростовской области на опытном поле ФГБНУ ФРАНЦ. Объекты исследований-урожайность и содержание белка в зерне ярового ячменя, возделываемого в звене севооборота горох-озимая пшеницаяровой ячмень. Закладка опытов, проведение учетов и математическая обработка полученных данных проводились согласно методике по… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One of the most important and timely topics of discussion is the upcoming climate change, both in the global project and in relation to the agriculture and crop production sectors [5][6][7]. A review of studies conducted in the last century revealed that in the continental climate of the Russian Federation, meteorological conditions are considered an important factor determining the average annual changes in the productivity of cultivated crops [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important and timely topics of discussion is the upcoming climate change, both in the global project and in relation to the agriculture and crop production sectors [5][6][7]. A review of studies conducted in the last century revealed that in the continental climate of the Russian Federation, meteorological conditions are considered an important factor determining the average annual changes in the productivity of cultivated crops [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the topical subjects of modern discussion is the problem of observed and upcoming climate changes, both globally and in relation to agronomy [3][4][5]. Studies conducted in the last century have shown that in the conditions of the continental climate of the Russian Federation, the most important factor determining the average annual changes in the productivity of cultivated crops is meteorological conditions [6][7].…”
Section: Introductionmentioning
confidence: 99%